2022
DOI: 10.3389/fcvm.2022.955838
|View full text |Cite
|
Sign up to set email alerts
|

Construction and analysis of competing endogenous RNA network and patterns of immune infiltration in abdominal aortic aneurysm

Abstract: BackgroundVarious studies have highlighted the role of circular RNAs (circRNAs) as critical molecular regulators in cardiovascular diseases, but its role in abdominal aortic aneurysm (AAA) is unclear. This study explores the potential molecular mechanisms of AAA based on the circRNA-microRNA (miRNA)-mRNA competing endogenous RNA (ceRNA) network and immune cell infiltration patterns.MethodsThe expression profiles of circRNAs (GSE144431) and mRNAs (GSE57691 and GSE47472) were obtained from the Gene Expression Om… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…CircRNAs, as a relatively novel research avenue in AAA, primarily exert their effects through miRNA sponging, possibly achieved through competitive endogenous RNA (ceRNA) mechanisms. Bioinformatics studies have explored potential molecular mechanisms in AAA by constructing ceRNA interaction networks involving circRNAs and miRNAs ( 85 ). For instance, circCBFB acts as a miR-28-5p sponge, promoting the reduction of GRIA4 and LYPD3 levels, thereby decreasing VSMC apoptosis and facilitating AAA progression ( 86 ).…”
Section: Epigenetic Mechanism Of Abdominal Aortic Aneurysmmentioning
confidence: 99%
“…CircRNAs, as a relatively novel research avenue in AAA, primarily exert their effects through miRNA sponging, possibly achieved through competitive endogenous RNA (ceRNA) mechanisms. Bioinformatics studies have explored potential molecular mechanisms in AAA by constructing ceRNA interaction networks involving circRNAs and miRNAs ( 85 ). For instance, circCBFB acts as a miR-28-5p sponge, promoting the reduction of GRIA4 and LYPD3 levels, thereby decreasing VSMC apoptosis and facilitating AAA progression ( 86 ).…”
Section: Epigenetic Mechanism Of Abdominal Aortic Aneurysmmentioning
confidence: 99%
“…circRNAs exert essential biological functions by sponging specific microRNAs (miRNAs), binding RNA-binding proteins, translating proteins, interfering with signalling pathways, and modulating transcription and splicing [ 11 , 12 , 13 , 14 ]. Construction of circRNA-miRNA-messenger RNA (mRNA) networks might help identify new potential diagnostic and therapeutic targets for diseases; for example, circ_0002722-miR-130-PPARG might be associated with the pathogenesis of abdominal aortic aneurysm; this finding thus provides potential therapeutic targets for abdominal aortic aneurysm [ 15 ]. A large number of studies have shown that circRNAs are involved in the occurrence and development of atherosclerosis and may be considered as targets for clinical treatment [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…12,13 In addition, clinical studies of AAA have shown an increase in the number of M2 macrophages in the lesion area, which is related to the pathologic type of the lesion and the development stage. 14 TCF3, which is an important transcription factor, is known as E2A 15 and has important roles in immune cell differentiation, embryonic development, and cancer. [16][17][18] TCF3 can be expressed in a variety of cells, including embryonic stem cells, mouse cardiomyocytes, 19 liver cancer cells, 20 and macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 In addition, clinical studies of AAA have shown an increase in the number of M2 macrophages in the lesion area, which is related to the pathologic type of the lesion and the development stage. 14…”
Section: Introductionmentioning
confidence: 99%